Howling the Elegy: Madness and Counterpublic Mourning in Ginsberg’s Long-Form Poems - Sharma, Pradip; Adhikari , Bibek (The Outlook: Journal of English Studies, 2026)
This paper explores counterpublic in mourning, madness, and memory as the triad themes in “Kaddish” and “Howl” by Allen Ginsberg. The close reading of “Kaddish” constructs memory as broken recursive process shaped by his mother’s loss, while “Howl” expands his private anguish into a public dissent against the institutionalized madness and social repression. The analysis of the selected parts of the poems foregrounds their move away from elegiac tradition and hooks on the Beat countercultural context which draws on counterpublics concept of Michael Warner, and genre theory. It also moves beyond the existing political and biographical Ginsbergian scholarship to further the textual interpretation with psychoanalytic and postmodern theoretical frameworks to demonstrate how Ginsberg repositions elegy as a hybrid mode of personal mourning and collective critique. Doing so, it argues that Ginsberg takes madness as a poetic strategy as a part of Beatnik movement to resist the American mainstream epistemology. His “creative insanity,” includes sexuality, and drug experience which disrupts normative boundaries between sanity and disorder that helps redefine elegy as an open-ended, performative discourse. It offers a nuanced reading of Beat poetics and elegiac form by resurfacing Ginsberg’s outlining of mourning as the poetic spaces of cultural and ideological contestation beyond classical elegy. It further suggests that such a framework can be an extended model to study modern and postmodern elegy that mingles personal grief with broader socio-political critique.